LANDASAN FAKTOR KEBIJAKAN IMPOR BERAS INDONESIA ASAL THAILAND PADA TAHUN 2009 – 2011 - Dewi, Citra Syafni; Pahlawan, Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research discussed about basic factor of policy import Indonesia Rice from Thailand in 2009-2011 and the purpose of this research is to find out reasons of Indonesia make a decision to import from Thailand. Rice have very important role in Indonesia citizen?s life in many aspect such as economy, labor, living environment, social, culture and politic. Indonesia has great potency in agriculture but the fact is there are so many farmers that weak in economy aspect. This is qualitative research which used descriptive explanative methods, and collecting datas from books, journals, articles, mass media, official publications and relevant websites. This paper used the liberalism perspective written by Locke, analysis unit nation-state and the theory is International Corporation written by K.J.Holsti. The result of this research is Indonesia makes decision to import rice from Thailand because domestic rice cannot sufficient. There are some reasons first, hard distributions, unstable climate, citizens always increase that make consume of rice also increase, Indonesian always think that rice is primer food. Honestly, Indonesia can be independent country in agriculture aspect especially for primary food in this country but need more attention from all sectors in order Indonesia can be develop country. Keyword: BULOG, HPP, International Corporation, Import, Rice